A.K. Sarbhoy Memorial Lecture Award* : Biodiversity of fungi in forests and their co-existence - Dr. Jamaluddin - JAMALUDDIN, Dr. (Indian Phytopathology, 2011)
The fungi exist in diverse habitats and they vary according to the substrates. A wide variety of habitat types can be expected to safeguard fungi in situ. The diverse groups of fungi occur in different forest types and it is a congenial habitat for this heterotrophic group of microbic world. The forest floor is rich in cellulose and lignin and a variety of fungi come in succession and flourish for the available food. Majority of fungi secrete different forms of enzymes to convert the complex substances suitable for utilization and metabolism. Ecology of fungi is considerably changed when it is associated with agriculture or forestry species as the forest plants have long gestation period. The diversity of higher fungi is less in agricultural crops while the forest ecosystem is dominated by the higher group of fungi. Many of the mycorrhizal fungi are eliminated by deforestation and plantation of other species. The plantation of source obstacle the reestablishment and survival of such associated fungi. Similarly, a large number of wood decay fungi are affected when they do not find mature trees or timber for decay. Many of the fungi are indicators of forest types or ecosystems.